A comprehensive study of DDoS attacks over IoT network and their countermeasures. Issue 127 (April 2023) - Kumari, Pooja; Jain, Ankit Kumar
Abstract: IoT offers capabilities to gather information from digital devices, infer from their results, and maintain and optimize these devices in different domains. IoT is heterogeneous in nature, which makes it prone to various security threats like confidentiality and integrity breaches, lack of availability of resources, trust issues, etc. The security concerns lead to different attacks over the system, and the Distributed Denial of Services (DDoS) bout is growing generously. DDoS is an assault that targets the availability of resources and servers of a network by flooding the communication medium from distinct locations by utilizing various IoT devices, which makes it harder to detect. Thus, analyzing and defending DDoS is a protruding field of research these days. The paper gives a thorough knowledge of DDoS over IoT. In this, we have critically analysed the existing DDoS variants, IoT Security issues, the execution of DDoS attempts, along with the exploitation of IoT devices and creation of them in Botnets or zombies. Moreover, the paper will also cover prevailing DDoS defense methodologies as well as their comparative analysis for ease of understanding.